Studies of Diboron Compounds Using Solid-State Multinuclear Magnetic Resonance Spectroscopy - Wong, Ying-Tung Angel (Université d'Ottawa / University of Ottawa, 2017)
The development of diboron derivatives has gained much attention lately due to the importance and the versatility of these compounds in synthetic and materials chemistry. Since chemical behavior is governed by electronic properties, insights into the bonding nature of these systems would be highly beneficial for the rational design of function-specific diboron motifs. In this thesis, the potential of the indirect spin-spin (J) coupling interaction in elucidating electronic structures of B-B bonds is illustrated. The J(11B, 11B) coupling constants of various heterocyclic diboron complexes and electron-precise diborane compounds bearing 2-center 2-electron (2c-2e) B(sp3)-B(sp3) bonds were measured using 11B double-quantum-filtered (DQF) J-resolved solid-state NMR (SSNMR) spectroscopy. Natural localized molecular orbital (NLMO) and natural bond orbital (NBO) analyses were also conducted in order to determine the electronic origin of the J couplings. The J(11B, 11B) coupling constants were found to reflect a plethora of bonding properties, ranging from the hybridization state and the strength of the B-B bonds, to the electron withdrawing capacity of the functional groups attached to the boron centers. Specifically, a strong correlation was obtained between the coupling constants and the hybridization state of the boron orbitals which form the B-B bond and the strength of the B-B bonds. These results show that electronic information, and thus chemical behavior, can be directly inferred from the J(11B, 11B) coupling constants. This is further illustrated by the studies on various diboratellurenium compounds. Using the relationship between the J coupling constants and the hybridization states, the B-B bond order of these compounds, which was found to be ambiguous by other commonly employed experimental methods, was determined. Moreover, given the vast interest in the dynamics studies of solids, such as the investigation of motions in molecular machines and metal organic frameworks, the development of new SSNMR techniques for probing dynamics can be valuable. In this thesis, the DQF J-resolved experiment is also presented as a novel tool for exploring molecular motions in solids. Using the electron-precise diborane compounds as archetypes, samples which experiences dynamic disorder were identified by 11B and 13C SSNMR experiments, and the results from variable-temperature (VT) experiments indicate the presence of three different motional processes in the temperature range of 248 to 306 K, occurring at a rate of 102 to 106 s-1. The molecular motions were found to manifest itself in the DQF J-resolved spectra in a predictable manner, where the DQF J splittings were observed to be amplified by a factor of 3 as compared to the theoretical J coupling constants if (1) the borons are static and crystallographically equivalent or (2) the borons are crystallographically inequivalent but magnetically equivalent on the time scale of the experiment as a result of dynamic disorder. Consequently, dynamic disorder must be taken into consideration when analyzing the data from DQF J-resolved experiments in order to correctly extract the J coupling constants, and conversely, these experiments can potentially be employed to detect the presence of dynamics in solids.
Keywords: Solid-state NMR spectroscopy; Diboron; Dynamics; Electronic structure; J coupling